A discipline of multiprogramming programming theory for distributed applications - Misra, Jayadev (Monographs in computer science, 2001)
Develops a programming model that addresses the fundamental issues of 'large-scale programming'. This title includes an approach that unifies several concepts from database theory, object-oriented programming and designs of reactive systems.